Search for sources of resistance to leaf diseases among present winter bread wheat varieties in the southern part of the Rostov region - T. G. Derova; N. V. Shishkin; М. М. Ivanisov; O. S. Kononenko (Зерновое хозяйство России, 2024)
The purpose of the current work was to search for sources of winter wheat varieties’ resistance to the most common pathogens of the area under artificial infectious backgrounds and recommend them for inclusion in the breeding process. The study was carried out on the experimental plots of the laboratory for plant immunity and protection of the FSBSI Agricultural Research Center “Donskoy” in 2021–2023. In order to expand the genetic diversity in immunity of newly developed varieties, it is necessary to use new sources of resistance. The objects of study were 78 winter wheat varieties from interstation variety testing, representing various breeding institutions in Russia and some foreign varieties. The study material was presented by the North Caucasian populations of pathogens of such wheat leaf diseases as powdery mildew, brown and yellow rust, and leaf spot (Septoria). Infectious backgrounds were formed according to generally accepted methods, using spore material of pathogens both stored and collected from crops in the previous year (types of rust) and collected from overwintered plants in the spring (powdery mildew, leaf spot). Weather conditions varied across the years of study (mainly in the autumn), but the damage to susceptible test varieties in the experiments was maximum. As a result of the study of the varieties on their resistance to one pathogen, there have been identified 23 varieties resistant to powdery mildew, 56 ones to leaf rust, 47 ones to yellow rust, 8 varieties to leaf spot. There has been given a characteristic of varieties according to various degree of resistance or susceptibility to each pathogen. On the resistance to two pathogens, there have been identified 17 varieties resistant to brown and yellow rust, 2 varieties resistant to brown rust and powdery mildew, 2 varieties resistant to yellow rust and powdery mildew, 1 variety resistant to brown rust and leaf spot. Ten varieties have shown resistance to no one pathogen, but they have had moderate resistance or moderate susceptibility to several other pathogens. 20 varieties were resistant to three diseases in various combinations, and 16 of them were resistant to brown, yellow rust, and powdery mildew. One variety ‘MV Nador’ from Hungary showed resistance to all 4 pathogens. All resistant varieties identified in the study can replenish the supply of winter wheat sources to the complex of leaf diseases for breeding purposes or be used in integrated crop protection against leaf diseases.